Efficacy and safety of Tuina (Chinese Therapeutic Massage) for knee osteoarthritis: A randomized, controlled, and crossover design clinical trial - Liu, Kaoqiang; Zhan, Yunfan; Zhang, Yujie; Zhao, Ye; Chai, Yongli; Lv, Hua; Yuan, Weian (Frontiers in Medicine, 2023)
Background: Knee osteoarthritis (KOA) is a highly prevalent joint disease among the middle-aged and elderly population, which can lead to pain, functional impairment, decreased quality of life, and a large number of medical expenses. Physical therapy is one of the main treatment methods for knee osteoarthritis. In China, Tuina has been widely used in the treatment of knee osteoarthritis, but up to now, there is no high-quality evidence-based medical evidence to support its effectiveness and safety. The purpose of this study was to objectively evaluate the efficacy and safety of Tuina in the treatment of KOA. Methods: A crossover design clinical trial was performed in 96 patients. The test group and the control group in the trail were allocated randomly in a ratio of 1:1. The test group received Tuina treatment for 4 weeks first, and then received health education intervention for another 4 weeks. The control group received health education intervention for 4 weeks first, and then received Tuina treatment for another 4 weeks. The Western Ontario and McMaster Universities Arthritis Index (WOMAC) total score was chosen as the primary outcome. WOMAC-pain score, WOMAC-stiffness, WOMAC- daily activity score, and Visual Analogue Scale (VAS) score were as the secondary outcome. Adverse events during the intervention were collected in both groups. Results: Compared with the baseline, the WOMAC-total score, WOMAC-pain score, WOMAC-stiffness, WOMAC-daily activity and VAS score of patients in both groups were improved significantly at week 4 and week 8 (p<0.001). All patients who received Tuina treatment were significantly superior to those who received health education intervention in WOMAC-total score (194.96, 95%CI=164.94 to 224.97, P<0.001), WOMAC-pain score (45.96, 95%CI=35.82 to 56.09, P<0.001), WOMAC-stiffness (31.42, 95%CI=26.37 to 36.46, P<0.001), WOMAC-daily activity (117.58, 95%CI=97.56 to 137.61, P<0.001), VAS-score (1.07, 95%CI=0.83 to 1.32, P<0.001). Both groups had no serious adverse events during treatment. Conclusion: This trial demonstrated that Tuina can reduce joint pain in patients with KOA and improve physical functions of the knee joint effectively and safely. Clinical Trial Registration: This trail was registered in Chinese Clinical Trail Registry on 22 March 2013(No. ChiCTR-TTRCC-13003157). URL:http://www.chictr.org.cn/showproj.aspx?proj=6402